Peran UMKM ( Usaha Mikro, Kecil, Menengah) Dalam Perekonomian Nasional - Amalina, Azkia Kia; Subiyantoro, Subiyantoro (LPPM Universitas Multi Data Palembang, 2024)
Abstract: This study aims to provide a new perspective on the study of entrepreneurship and its relation to the progress of the Indonesian economy And this research uses the literature study method (Library Reserch) and the data obtained in this study will be analyzed by descriptive analysis through literature studies so that studies can be carried out from related sources using data sources Secondary data in the form of data that has been published in the form of e-books, articles, websites and so on that have a relationship in this study. This research aims to provide a new perspective on the study of entrepreneurship based on micro, small, medium enterprises, and their relation to the progress of the Indonesian economy and provide evaluation materials to stakeholders so that entrepreneurship can contribute to the progress of the Indonesian economy. In general, UMKM in the national economy have a role as the main player in economic activities; employment providers; important players in local economies and community empowerment; creators of new markets; and its contribution to PDB and balance of payments. One way to find out the role of UMKM in the economy is through PDB.